2008
DOI: 10.1016/j.bandl.2007.11.004
|View full text |Cite
|
Sign up to set email alerts
|

How left inferior frontal cortex participates in syntactic processing: Evidence from aphasia☆

Abstract: We report on three experiments that provide a real-time processing perspective on the poor comprehension of Broca's aphasic patients for non-canonically structured sentences. In the first experiment we presented sentences (via a Cross Modal Lexical Priming (CMLP) paradigm) to Broca's patients at a normal rate of speech. Unlike the pattern found with unimpaired control participants, we observed a general slowing of lexical activation and a concomitant delay in the formation of syntactic dependencies involving "… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

16
158
5

Year Published

2009
2009
2024
2024

Publication Types

Select...
9
1

Relationship

0
10

Authors

Journals

citations
Cited by 106 publications
(179 citation statements)
references
References 65 publications
16
158
5
Order By: Relevance
“…Therefore, one way to explain both our finding and that of previous aging syntax research is that, whereas underlying syntactic representations do not change with age, the ability to access the representations of complex syntactic structures in unsupported (i.e., unprimed) situations does decline in old age. This explanation draws parallels with a debate in the aphasia literature, specifically whether aphasia results in a complete degradation of syntactic knowledge (Grodzinsky, 1984(Grodzinsky, , 2000 or just a loss of rapid access to the relevant syntactic knowledge (Burkhardt, Avrutin, Piñango, & Ruigendijk, 2008;Love, Swinney, Walenski, & Zurif, 2008). Indeed, there is evidence that syntactic priming is maintained in aphasics despite profound impairments in language production and comprehension (Hartsuiker & Kolk, 1998;Verreyt et al, 2013).…”
Section: Discussionmentioning
confidence: 73%
“…Therefore, one way to explain both our finding and that of previous aging syntax research is that, whereas underlying syntactic representations do not change with age, the ability to access the representations of complex syntactic structures in unsupported (i.e., unprimed) situations does decline in old age. This explanation draws parallels with a debate in the aphasia literature, specifically whether aphasia results in a complete degradation of syntactic knowledge (Grodzinsky, 1984(Grodzinsky, , 2000 or just a loss of rapid access to the relevant syntactic knowledge (Burkhardt, Avrutin, Piñango, & Ruigendijk, 2008;Love, Swinney, Walenski, & Zurif, 2008). Indeed, there is evidence that syntactic priming is maintained in aphasics despite profound impairments in language production and comprehension (Hartsuiker & Kolk, 1998;Verreyt et al, 2013).…”
Section: Discussionmentioning
confidence: 73%
“…Such an absence of priming effects restricted to Broca's aphasia was originally interpreted as consistent with the hypothesis of deleted traces (TDH) and impaired syntactic processing. Later studies, however, demonstrated that, although reactivation of the antecedent of the trace may be absent at the trace/gap-site, the effect can still be observed in Broca's aphasia, although in a delayed fashion at later points in the sentence (Burkhardt, Pinango, & Wong, 2003;Love, Swinney, Walenski, & Zurif, 2008;Love, Swinney, & Zurif, 2001). Interestingly, gap-filling effects similar to those of unimpaired listeners can still be found in Broca's aphasia when sentences are presented with a slower-than-normal speech rate and, therefore, with a gap-site that is longer lasting (Love et al, 2008).…”
Section: Other Online Methods In Research On Aphasic Sentence Processingmentioning
confidence: 95%
“…This impairment is typically associated with lesions that include Broca's area (left IFG, including Brodmann areas 44 and 45) (e.g., Alexander, Naeser, & Palumbo, 1990;Zurif, 1995). The left IFG has been consistently linked to syntactic processing, across a wide range of approaches and methods (Berndt & Caramazza, 1980;Caplan, Alpert, & Waters, 1998Constable et al, 2004;Damasio & Damasio, 1989;Dapretto & Bookheimer, 1999;Embick, Marantz, Miyashita, O'Neil, & Sakai, 2000;Friedmann & Shapiro, 2003;Grodzinsky, 2000Grodzinsky, , 2006Love, Swinney, Walenski, & Zurif, 2008;Luke, Liu, Wai, Wan, & Tan, 2002;Stromswold, Caplan, Alpert, & Rauch, 1996;Swinney & Zurif, 1995;Zurif, 1995). Specifically, brain imaging studies have reported consistent activations in Broca's area in response to sentences that are derived by syntactic movement, such as relative clauses and topicalization, structures that have been tested in the current study as well, and which load onto the CP layer (Ben-Shachar, Hendler, Kahn, Ben-Bashat, & Grodzinsky, 2003;Ben-Shachar, Palti, & Grodzinsky, 2004;Constable et al, 2004;Grodzinsky & Friederici, 2006;Grodzinsky & Santi, 2008;Just, Carpenter, Keller, Eddy, & Thulborn, 1996;Stromswold et al, 1996).…”
Section: Brain Function and The Syntactic Deficitmentioning
confidence: 97%